Follicular lymphoma in children and adolescents: clinical, diagnostic and therapeutic features - T. T. Valiev; A. S. Volkova; M. A. Postoykina; D. S. Abramov; A. R. Karibova; A. A. Odzharova; Yu. E. Ryabukhina; P. A. Zeynalova (Онкогематология)
Ffollicular lymphoma (FL) is one of the most common non-Hodgkin’s lymphomas in adults, while it is a diagnosis of exclusion in adolescents and children. Clinical manifestations of FL in children are represented by long-term asymptomatic lymphadenopathy, less commonly by extranodal areas involvement. treatment standards for FL in children have not been developed and may vary from observational tactics (with the radical resection of a single focus during a biopsy) to the use of radiation therapy and polychemotherapy. Pediatric type follicular lymphoma was first identified as a distinct variant in 2008 in the world Health organization classification of hematopoietic and lymphoid tissue tumors. Clinical, morphological (cytological type 3A), Immunohistochemical (absence of bcl2 expression in the center of the follicle) and cytogenetic (absence of t(14;18)(q32;q21)) features served as the reason for separation into an independent nosological variant. Despite the term “pediatric”, cases of pediatric type FL have been described in adults over 30 years of age. Most often, the disease is diagnosed in the early stages (I, II) and is characterized by a favorable prognosis. In children and adolescents, FL occurs not only of the pediatric type. we present a clinical case of a typical “adult” type FL (grade 1–2) in a 17-year-old patient. the cHop therapy (cyclophosphamide, doxorubicin, vincristine, and prednisolone) with rituximab resulted in a complete remission, which lasted more than 2.5 years.